Increased Bone Marrow-Specific Adipogenesis by Clofazimine Causes Impaired Fracture Healing, Osteopenia, and Osteonecrosis Without Extraskeletal Effects in Rats. (8th August 2019) - Porwal, Konica; Pal, Subhashis; Tewari, Deepshikha; Pal China, Shyamsundar; Singh, Priya; Chandra Tewari, Mahesh; Prajapati, Gurudayal; Singh, Pragati; Cheruvu, Srikanth; Khan, Yasir A; Sanyal, Sabyasachi; Gayen, Jiaur R; et al.
Abstract: Mycobacterium leprae infection causes bone lesions and osteoporosis, however, the effect of antileprosy drugs on the bone is unknown. We, therefore, set out to address it by investigating osteogenic differentiation from bone marrow (BM)-derived mesenchymal stem cells (MSCs). Out of 7 antileprosy drugs, only clofazimine (CFZ) reduced MSCs viability (IC50  ∼ 1 μM) and their osteogenic differentiation but increased adipogenic differentiation on a par with rosiglitazone, and this effect was blocked by a peroxisome proliferator-activated receptor gamma antagonist, GW9662. CFZ also decreased osteoblast viability and resulted in impaired bone regeneration in a rat femur osteotomy model at one-third human drug dose owing to increased callus adipogenesis as GW9662 prevented this effect. CFZ treatment decreased BM MSC population and homing of MSC to osteotomy site despite drug levels in BM being much less than its in vitro IC50 value. In adult rats, CFZ caused osteopenia in long bones marked by suppressed osteoblast function due to enhanced adipogenesis and increased osteoclast functions. A robust increase in marrow adipose tissue (MAT) by CFZ did not alter the hematologic parameters but likely reduced BM vascular bed leading to osteonecrosis (ON) characterized by empty osteocyte lacunae. However, CFZ had no effect on visceral fat content and was not associated with any metabolic and hematologic changes. Levels of unsaturated fatty acids in MAT were higher than saturated fatty acids and CFZ further increased the former. From these data, we conclude that CFZ has adverse skeletal effects and could be used for creating a rodent ON model devoid of extraskeletal effects.